Fatigue during exercise - Szygula, Z.; Gawronski, W.; Kalinski, M. I. (Medicina Sportiva, 2003)
Fatigue is a physiological state occurring during engagement in a physical or mental activity. It lowers performance levels, decreases the speed of movements or causes complete work discontinuation. There are two different patterns of fatigue . one, the pattern being the effect of short-term effort of high-intensity and second, the pattern as the result of long-term exercise. Energetic insufficiency plays an important role in the etiology of muscle fatigue. The other most common changes associated with fatigue are: accumulation of acidic metabolic by-products in working muscles, and finally, the failure of the contractile mechanisms in the muscle fiber. Also described are the alterations in metabolism of some neurotransmitters in central nervous system occurring during exercise, depicted as central fatigue. The paper discusses changes occurring during short-term intensive exercise and long-term exercise, respectively.